Exploring the impact of gamified learning on positive psychology in CALL environments: A mixed-methods study with Thai university students - Budi Waluyo; Francis G. Balazon (Acta Psychologica)
Despite growing interest in both fields, research into how positive psychology principles and gamification can be integrated in Computer-Assisted Language Learning (CALL) environments and their impact on language learning outcomes remains insufficiently explored. Thus, this study intends to contribute by implementing a 10-week gamified learning program using the Quizizz application within CALL classrooms at a university in Thailand. A total of 69 first-year students, experiencing gamified learning—which integrates game elements into educational activities—for the first time, participated in this sequential explanatory mixed-method study, which combined a single-group design with narrative frames. After a one-week introduction to the course, the study progressed through two cycles—Cycle 1 spanned five weeks, and Cycle 2 lasted four weeks. Throughout these periods, we collected data using surveys, test scores, and narrative frames. Quantitative data were analyzed using descriptive and inferential statistics, while narrative essays were examined using thematic analysis. The study found that positive psychology principles such as motivation, enjoyment, and anxiety remained stable over the two learning cycles, indicating that while gamified learning initially engages students, its effects do not significantly evolve without varied interventions. Even with high initial motivation and enjoyment, there were only modest improvements in reducing anxiety, suggesting that competitive elements in gamified environments might sustain some anxiety levels. Additionally, strengthened interrelationships among motivation, enjoyment, anxiety, and performance were observed, but these psychological factors did not directly predict grammar test outcomes.